EURO-MUSCULUS/USPRM Dynamic Ultrasound Protocols for Ankle/Foot - Pirri, Carmelo; Stecco, Carla; Güvener, Orhan; Mezian, Kamal; Ricci, Vincenzo; Jačisko, Jakub; Fojtik, Petr; Kara, Murat; Chang, Ke-Vin; Dughbaj, Muhammad; Özçakar, Levent (American journal of physical medicine & rehabilitation, 2024)
In this dynamic scanning protocol, ultrasound examination of the ankle is described using various maneuvers to assess different conditions. Real-time patient examination and scanning videos are used for better simulation of daily clinical practice. The protocol is prepared by several/international experts in the field of musculoskeletal ultrasound and within the umbrella of European Musculoskeletal Ultrasound Study Group in Physical and Rehabilitation Medicine/Ultrasound Study Group of the International Society of Physical and Rehabilitation Medicine.
Keywords: Musculoskeletal System; Foot; muskuloskeletální systém; Musculoskeletal Diseases; noha (od hlezna dolů); lidé; rehabilitační lékařství; kotník; muskuloskeletální nemoci; Ultrasonography; Physical and Rehabilitation Medicine; Ankle; ultrasonografie; Humans